Total synthesis of (-)-radicamine B - Gurjar, Mukund K.; Borhade, Ramdas G.; Puranik, Vedavati G.; Ramana, C. V. (Tetrahedron Letters, 2006)
The synthesis of a chiral cyclic nitrone with L-arabino configuration and its application in the total synthesis of radicamine B is reported. An agreement in the spectral data with natural radicamine B but specific rotation with an opposite sign warranted a revision of the absolute configuration of radicamine B. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: codonopsinine; Cyclic nitrone; Grignard addition; polyhydroxy pyrrolidine alkaloids; radicamine B

Total synthesis of pachastrissamine (jaspine B) enantiomers from D-glucose - Ramana, C. V.; Giri, Awadut G.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Synthesis of both enantiomers of pachastrissamine is described from a common chiral template. The stereoselective construction of the central tetrahydrofuran units was based on the pseudodesymmetrization of a pentodialdo-1,4-furanose derivative taking advantage of the latent symmetry present. (c) 2006 Published by Elsevier Ltd.
Keywords: 4-furanose; chiron approach; Ohira-Bestmann reaction; pachastrissamine/jaspine B; pentodialdo-1; ring isomerization

Total synthesis and determination of relative and absolute configuration of multiplolide A - Ramana, C. V.; Khaladkar, Tushar P.; Chatterjee, Soumitra; Gurjar, Mukund K. (Journal of Organic Chemistry, 2008)
A flexible approach for total syntheses of possible multiplolide A diastereomers establishing the relative and absolute configuration is documented. The adopted strategy features ring-closing metathesis (RCM) as the key reaction and screening of a set of substrates for the feasibility of RCM in general and for the requisite E-configuration of ring olefin in particular. Selective protecting groups manipulation prior to the assembly of the central macrocyclic core was instrumental in installing the epoxide functionality on a fully deprotected nonenolide at the end of the synthesis.

Target cum flexibility: an alkyne [2+2+2]-cyclotrimerization strategy for synthesis of trinem library - Ramana, C. V.; Dushing, Mangesh P.; Mohapatra, Sradhanjali; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron Letters, 2011)
A rapid access to the central 4,5,6-tricyclic core of 4,5,6-trinems has been achieved by employing the alkyne [2+2+2]-cyclotrimerization as the key and final reaction in the synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Target cum flexibility: synthesis of C(3 `)-spiroannulated nucleosides - Dushing, Mangesh P.; Ramana, C. V. (Tetrahedron Letters, 2011)
We report a simple strategy for the synthesis of a collection of C(3')-spirodihydroisobenzo-furannulated nucleosides featuring a [2+2+2]-cyclotrimerization as the key reaction. The cyclotrimerization reactions are facile with the unprotected nucleosides having a diyne unit. When both alkynes of the diyne are terminal, the regioselectivity is poor. However, when one of the terminal alkynes is additionally substituted, the cyclotrimerizations are highly diastereoselective. Since the key bicycloannulation is the final step, this strategy provides flexibility in terms of the alkynes and is thus amenable for the synthesis of a focussed small molecule library. (C) 2011 Published by Elsevier Ltd.
Keywords: Dihydroisobenzofuran; Modified nucleosides; Tanaka catalyst; Willkinson catalyst; [2+2+2]-Cyclotrimerization

Totall synthesis of (+/-)-sacidumllignan D - Pandey, Sunil Kumar; Ramana, C. V. (Journal of Organic Chemistry, 2011)
The first total synthesis of (+/-)-sacidumlignan D featuring a Zn-mediated Barbier reaction and reverse Wacker oxidation to form the key gamma-lactone, its diastereoselective alpha-methylation followed by reduction cyclization, was documented.

Total synthesis of (-)-isatisine A - Patel, Pitambar; Ramana, C. V. (Journal of Organic Chemistry, 2012)
A modular total synthesis of (-)-isatisine A is described in which four consecutive metal-mediated transformations have been employed at the final stage. These include [Pd]-catalyzed Sonogashira coupling, [Pd]-catalyzed nitroalkyne cycloisomerization leading to isatogens, and addition of indoles to isatogens using InCl3- and [Rh]-catalyzed oxidative N-heterocyclization of amino alcohol to form the key amide bond. In addition to these, the removal of the protecting groups has also been carried out in a selective fashion employing either catalytic or stoichiometric metal/metal-based reagents.

Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium

Total synthesis of mangiferaelactone - Vadhadiya, Paresh M.; Ramana, C. V. (Tetrahedron Letters, 2014)
Herein we document the first total synthesis of mangiferaelactone and thus establish its absolute configuration. The central nonenolide ring was constructed using ring closing metathesis and Yamaguchi esterification. The key alcohol fragment was synthesized by the Bernet-Vasella fragmentation of C-ribofuranoside. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bernet-Vasella fragmentation; Nonenolide; Ring closing metathesis; Total synthesis; Yamaguchi protocol

Total synthesis of naturally occurring cephalosporolides E/F - Kona, Chandrababu Naidu; Ramana, C. V. (Tetrahedron, 2014)
A modular total synthesis of cephalosporolides E/F featuring sequential epoxide-alkyne coupling and subsequent highly regioselective gold catalyzed alkynolcycloisomerizatio of the resulting alkynetetrol to construct the central spiroketal core has been documented. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Alkynetetrol; Cephalosporolide; Epoxide-alkyne coupling; Gold catalysis; Spiroketalization